Microalgal hydrogen production : achievements and perspectives - Seibert, Michael; Torzillo, Giuseppe (Royal Society of Chemistry, 2018)
This title documents the increased interest in achievements in the field of light-driven, microalgal hydrogen production and the bottlenecks currently preventing exploitation of the technology in the practical arena.
Keywords: Hydrogen -- Biotechnology.; Hydrogen as fuel.; Algae -- Biotechnology.; elektronické knihy; electronic books